Technical testing and match analysis statistics as part of the talent development process in an English football academy - Kelly, A.; Wilson, M. R.; Jackson, D. T.; Williams, C. A. (International Journal of Performance Analysis in Sport, 2020)
Technical ability is recognised as a fundamental prerequisite to achieve senior professional status in football. However, research is yet to investigate what technical attributes contribute to greater coach perceived potential within an academy environment. Therefore, the aim of this study was to examine technical ability and skill behaviour as contributing factors to coach potential ratings in an English football academy. Ninety-eight outfield academy players (Foundation Development Phase [FDP] under-9 to under-11 n= 40; Youth Development Phase [YDP] under-12 to under-16 n= 58) participated in the study. Four football-specific technical tests were used to measure technical ability, whilst eight match analysis statistics from competitive match-play across an entire season were observed to measure skill behaviour. A classification of "higher-potentials" (top third) and "lower-potentials" (bottom third) were applied through coach rankings. Within the FDP, higher-potentials performed significantly better (P< 0.05) on the lob pass test, alongside greater reliability in possession, pass completion, and total touches for match analysis statistics. Within the YDP, higher-potentials performed significantly better (P< 0.05) on all four technical tests, alongside greater reliability in possession, dribble completion, and total touches for match analysis statistics. Results suggest football-specific technical tests and "in possession" skill behaviours may provide discriminative tools that align with perceived potential.